Nutritional Status and Family Background Analysis of Health Behavioral Factors - Radin Purnama Wuni; Endang Sri Wahjuni; Sapto Wibowo (Budapest International Research and Critics University, 2022)
This study aims to analyze the relationship between nutritional status and family background on health behavioral factors which include eating and drinking behavior, alcohol consumption behavior, drug consumption behavior, personal hygiene, physical activity, protective factors, smoking behavior, and violence and injury during the Covid 19 pandemic as it is today in teenagers in Pasuruan City. This study used a non-experimental research design with a survey method. Data collection uses the 2015 Indonesia Global School-Based Student Health Survey which was adopted from the World Health Organization (WHO) in 2015 and uses a descriptive quantitative approach with the aim of accurately describing the existing data. In this study, the population of this study were all high school students in Pasuruan City, and the respondents in this study were X grade students in 4 Pasuruan City Public High Schools with a total of 131 participants consisting of male and female students. woman. Analysis of the data used is the percentage, Chi-Square, and the Generalized Linear Model (GLM) gamma log ink. From the results of existing research, it can be seen that nutritional status does not have a significant relationship with health behavioral factors as evidenced by significant values, each of which is more than an alpha 0.05. Meanwhile, family background has a very complex relationship, such as the level of parental education has a significant relationship with students' physical activity, father's occupation has a significant relationship to alcohol consumption behavior, mental health, and protective factors. Overall, the description of the health behavior of students in Pasuruan City which is in the less category is 0.8% (1 person), the sufficient category is 62.6% (82 people), and the good category is 36.6% (48 people). Also, it can be seen that nutritional status and family background do not have a significant relationship with health behavior. But on the other hand, there is a variable that has the strongest relationship with the health behavior of students at SMAN Pasuruan City is the father's income.